How do working memory capacity and math anxiety affect the creative reasoning abilities of prospective mathematics teachers? - Hasan, Buaddin; Juniati, Dwi; Masriyah, Masriyah (Edelweiss Applied Science and Technology, 2025)
Creative reasoning involves generating new ideas and finding unusual solutions to a problem using an innovative approach. Creative reasoning allows individuals to develop diverse problem-solving strategies. However, mathematics anxiety, as an affective domain in mathematics learning, can inhibit cognitive performance in problem-solving. This research examines the impact of working memory capacity and mathematics anxiety and describes the creative reasoning process in solving mathematical problems. The sample of this study consisted of 62 prospective mathematics teacher students. This research employed a mixed-methods sequential explanatory design. The test scores were analyzed using multiple linear regression tests with an alpha level of .05. Meanwhile, qualitative data were collected for the second stage based on observations, geometric problem-solving tasks, and interviews. Qualitative data were analyzed in three phases: data presentation, reduction, and conclusion drawing. The results show that working memory capacity and mathematics anxiety influence the creative reasoning of prospective mathematics teachers in solving mathematical problems. Prospective mathematics teachers with high working memory capacity are flexible and fluent in their thinking, encouraging them to use novel ideas to solve problems. In addition, they can put forth logical arguments grounded in correct basic mathematical concepts. However, high mathematical anxiety may interfere with their thinking ability and inhibit their performance. When faced with a complex mathematical problem, they make incorrect answers. On the other hand, subjects with low working memory capacity are less flexible in thinking, which prevents them from using novel ideas when solving problems.